ASI EKSKLUSIF MENINGKATKAN PERKEMBANGAN BAYI USIA 6-12 BULAN DI WILAYAH KERJA PUSKESMAS BANYU URIP SURABAYA - Siti Nurjanah (Jurnal Ilmiah Kesehatan, 2015)
Exclusive Breast Milk Enhances The Development Of Infants Aged 6-12 Months in Region of Puskesmas Banyu Urip Surabaya. Exclusive breastfeedingis only giving breast without other suplemntal food to babies aged 6-12 months. However in factmost mothers do not give breast milk to their childrenby reason of busywork. The purpose of this study to analyzethe relationship between Exclusive Breast Milk enhances the development of infants aged 6-12 months in region of Puskesmas Banyu Urip Surabaya. The type of this research wasanalytic done using by cross sectional design. The population involved themothers having children aged 6-12 monthsand thei rchildren totally 28 respondents, the sample size was 26 respondents taken by using simple random sampling. The data collection using question naires and observation of DDST form. The data processing includes editing, coding, data entry, cleaning, and tabulating. The data were analyzed using the Mann-Whitney statistical testwith asignifican cevalue α=0,05. Statistical analysis with the Mann-Whitney was got r=0,000<α=0,05, whichmeans that H0 isrejectedso that there isa correlation between exclusive breastfeeding . With the Mann-Whitney was got r=0,002<α=0,05, whichmeans thatH0 isrejected so tha tthere isa correlation between exclusive breastfeeding and the development of children aged 6-12 months in East Java. The conclusions of this research is exclusive breastfeeding is adequate and the developmentof the child within the normal rangesaccording to age. Expectedmothersto breast feed exclusively thoughthe motherwas busyworking, andalwayspay attention totheir children's growth. So as to createa great newgeneration.